Congenital occipitoatlantoaxial malformation in a Warmblood mare. (22nd August 2017) - Brünisholz, H. P.; Wildhaber, N.; Hoey, S.; Ruetten, M.; Boos, A.; Kümmerle, J. M.
Summary: A 3‐year‐old Warmblood mare was presented with spinal ataxia of 3 months' duration. Clinically, reduced mobility of the neck and a prominent atlas were identified. Neurological evaluation revealed hypermetria, circumduction and reduced proprioception, predominantly in the hindlimbs. Occipitoatlantoaxial malformation (OAAM) was diagnosed based on radiography and computed tomography, and confirmed on post‐mortem magnetic resonance imaging and pathological examination. Both the atlas and axis were hypoplastic and dysplastic, and a fusion of the atlanto‐occipital joint was found. A dynamic compression of the spinal cord was present at the first and second cervical vertebrae. Histologically, the spinal cord was degenerated due to compression. Furthermore, there were muscular malformations including a fibrotic obliquus capitis cranialis muscle, aplasia of parts of the rectus capitis muscles and presence of additional abnormal muscle. Such muscular abnormalities associated with OAAM have not been reported yet and this is the first report of a case of OAAM in a Warmblood horse.